Relative efficacy of catheter ablation vs antiarrhythmic drugs in treating premature ventricular contractions: A single-center retrospective study - Zhong, Li; Lee, Ying-Hsiang; Huang, Xin-Miao; Asirvatham, Samuel J.; Shen, Win-Kuang; Friedman, Paul A.; Hodge, David O.; Slusser, Joshua P.; Song, Zhi-Yuan; Packer, Douglas L.; Cha, Yong-Mei (Heart rhythm, 2014)
It is unknown whether radiofrequency ablation (RFA) or antiarrhythmic therapy is superior when treating patients with symptomatic premature ventricular contractions (PVCs). To determine the relative efficacy of RFA and antiarrhythmic drugs (AADs) on PVC burden reduction and increasing left ventricular systolic function. Patients with frequent PVCs (>1000/24 h) were treated either by RFA or with AADs from January 2005 through December 2010. Data from 24-hour Holter monitoring and echocardiography before and 6–12 months after treatment were compared between the 2 groups. Of 510 patients identified, 215 (40%) underwent RFA and 295 (60%) received AADs. The reduction in PVC frequency was greater by RFA than with AADs (–21,799/24 h vs –8,376/24 h; P < .001). The left ventricular ejection fraction (LVEF) was increased significantly after RFA (53%–56%; P < .001) but not after AAD (52%– 52%; P = .6) therapy. Of 121 (24%) patients with reduced LVEF, 39 (32%) had LVEF normalization to 50% or greater. LVEF was restored in 25 of 53 (47%) patients in the RFA group compared with 14 of 68 (21%) patients in the AAD group (P = .003). PVC coupling interval less than 450 ms, less impaired left ventricular function, and RFA were independent predictors of LVEF normalization performed by using multivariate analysis. RFA appears to be more effective than AADs in PVC reduction and LVEF normalization.